Efeito de adubações orgânica e mineral associadas ao biochar sobre parâmetros do solo e produtividade da alface - Pereira, Dercio Ceri (2016)
Applications of mineral fertilizer, mineral fertilizer with biochar, organic compost and organic compost with biochar were evaluated by leaf analysis to evaluate the performance of fertilizers associated or not to the biochar on lettuce. The results showed that the organic compost and mineral fertilizer meet the nutritional demands of lettuce. The use of biochar in fertilization does not affect lettuce productivity nor soil properties. The organic compost increases lettuce crop yield from the sixth cropping. The residual of the organic compound in the soil increased pH, electrical conductivity, carbon results. They have also shown accumulations of phosphorus potassium, copper, zinc, iron and manganese, as well as improved soil quality. The organic compost provides stability on soil respiration and activities of enzymes such as acid phosphatase, alkaline phosphatase and urease.